A pilot study of symptom profiles from a polyp vs an eosinophilic‐based classification of chronic rhinosinusitis. Issue 5 (18th December 2015) - Thompson, Christopher F.; Price, Caroline P.E.; Huang, Julia He; Min, Jin‐Young; Suh, Lydia A.; Shintani‐Smith, Stephanie; Conley, David B.; Schleimer, Robert P.; Kern, Robert C.; Tan, Bruce K.
Abstract : Background: Chronic rhinosinusitis (CRS) is likely a biologically heterogeneous disease process. Current guidelines propose subclassification using polyp status while others propose using mucosal eosinophilia. We hypothesized that appropriate CRS subclassification would increase homogeneity of baseline symptoms, and identify characteristic symptoms of each subtype. Methods: A total of 57 CRS patients undergoing surgery prospectively completed a preoperative battery of 73 questions relating to symptoms including the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and 29‐item Patient‐Reported Outcomes Measurement Information System (PROMIS‐29) general quality of life (QOL) measures. Eosinophilic cationic protein (ECP) levels were determined from ethmoid, uncinate, and polyp tissue homogenates using enzyme‐linked immunosorbent assay (ELISA) and normalized to total protein. Patients were classified as eosinophilic (eCRS) or non‐eosinophilic (neCRS) using a 95th percentile threshold established from control tissue from 82 patients without CRS. Separate pairwise comparisons were performed on patient‐reported symptoms using polyp and eosinophilic status. Results: Of the 57 patients, 28 had CRS with nasal polyps (CRSwNP); 27 of 57 patients had eCRS (CRSwNP, n = 21; CRS without nasal polyps [CRSsNP], n = 6). CRSwNP patients had increased need to blow nose, frequency of nasal congestion, more severe difficulty breathing through nose, more severe nasal discharge, but less cough ( p < 0.05). eCRS patients had more bothersome loss of taste/smell, ear pain, sneezing, severe difficulty breathing through nose, and severe nasal congestion compared to neCRS patients ( p < 0.05). Conclusion: Subclassifying CRS with symptoms alone is difficult with neither polyp status nor eosinophilia giving a distinctive clinical symptom profile. However, certain symptoms may help otolaryngologists identify CRS subtypes, which may help guide future treatments. Further validation and evaluation of prognosis following treatment is required to evaluate appropriate means of subclassifying CRS.